2013
DOI: 10.1002/pits.21718
|View full text |Cite
|
Sign up to set email alerts
|

Improving Employment Outcomes Among Adolescents and Adults on the Autism Spectrum

Abstract: As the number of diagnosed cases of ASD increases, school professionals must consider not only efficacious teaching approaches for improving academic goals, but also what systems must be in place to address one of the most important jobs of the school systems: preparing capable citizens. For more than 160 years, schools have been tasked with preparing good citizens who are capable of contributing to society through work. Given the fact that schools have been required to provide appropriate educational programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 55 publications
0
37
1
Order By: Relevance
“…Employers' Attitudes It is important to consider employers' characteristics and how they interact with individuals with ASD, because these factors ultimately determine whether people get a job and how he/she sustains the position (Vornholt et al 2013;Wilczynski et al 2013). López and Keenan (2014) conducted a survey that demonstrated that "lack of appropriate understanding from employers and coworkers" is one of the biggest barriers to successful employment.…”
Section: External Challenging Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Employers' Attitudes It is important to consider employers' characteristics and how they interact with individuals with ASD, because these factors ultimately determine whether people get a job and how he/she sustains the position (Vornholt et al 2013;Wilczynski et al 2013). López and Keenan (2014) conducted a survey that demonstrated that "lack of appropriate understanding from employers and coworkers" is one of the biggest barriers to successful employment.…”
Section: External Challenging Factorsmentioning
confidence: 99%
“…As a necessary component of adult life, employment is one of the most desirable achievements for every individual, including people with ASD, when we enter our adulthood (Bennett and Dukes 2013;Roux et al 2013;Wilczynski et al 2013. Successful employment increases an individual's social status and financial independence and maintains a person's physical and psychological health, thereby improving his/her quality of life (Fleming et al 2013;Gerhardt and Lainer 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Supported employment represents an integrated model of employment where workers with disabilities are assisted throughout the employment process and work in community-based settings (Gottlieb et al 2010). Competitive employment involves people with disabilities working at an equivalent rate to those without disabilities, and research illustrates that between 6 and 10 % of individuals with ASD are competitively employed (Wilczynski et al 2013). Although these employment options exist, positions are limited and are typically directed toward individuals who are high functioning (Sonne 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, their performance was maintained at follow-up. KEYWORDS autism spectrum disorder, behavioral skills training, InterviewStream©, job interview training 1 | INTRODUCTION paid less than their neurotypical peers (Wilczynski, Trammell, & Clarke, 2013). Individuals with ASD may present difficulties with a variety of behaviors related to social skills including eye contact, engaging in reciprocal conversation, and initiating or responding to another person's interactions.…”
mentioning
confidence: 99%